Photoconductive, dielectric and percolation properties of anodic TiO2 nanotubes studied by terahertz spectroscopy - Kuchařík, Jiří; Sopha, Hanna; Krbal, Milos; Rychetský, Ivan; Kužel, Petr; Macák, Jan; Němec, Hynek (IOPscience, 2017)
Self-organized layers of anodic TiO2 nanotubes were investigated using time-resolved terahertz spectroscopy in the steady state and upon photoexcitation. The interpretation of the conductivity spectra is based on the response of confined charges calculated by the Monte-Carlo method and on the evaluated distribution of the probing terahertz electric field in the heterogeneous structure. We show that the charge motion perpendicular to the nanotube axis is confined on ~10 nm scale, and that the charge mobility inside these confinement areas is comparable to that observed in a bulk anatase crystal. The electrical connectivity between individual nanotubes assessed from the terahertz spectra qualitatively correlates with the geometry observed in SEM images. The measured transient terahertz transmission spectra feature an apparent resonance; we demonstrate that it is not a signature of a new low-energy excitation but a geometrical effect of Fabry-Pérot interferences in the photoexcited slab.
Keywords: anodic TiO2 nanotubes; terahertz spectroscopy; charge transport; dielectric properties